Sustainable Catalytic Processes for the Valorisation of Light Alcohols - Malmusi, Andrea <1988> (Alma Mater Studiorum - Università di Bologna, 2016)
During my PhD I carried out three main research works, which are described in this thesis. The topics of my research were dealt with the development of more sustainable processes through the exploitation of renewable sources and the replacement of hazardous chemicals with safer ones. Two of the three research topics I carried out dealt with ethanol as a renewable source for the development of more sustainable processes. Another research topic concerned isobutene alkylation with methanol, as a substitute for formaldehyde. First research project was regarding ethanol transformation over V-based catalysts. Fe/V and Cu/V mixed oxides were tested as catalysts for the transformation of ethanol both in aerobic and anaerobic conditions. Both catalysts were active in ethanol dehydrogenation to acetaldehyde. Anyway the presence of Fe or Cu had an influence on catalytic performance. The reason of these different behaviours were investigated by means of characterization techniques. Another research work, regarding ethanol as raw material, was carried out during my stage at the Lieibniz Institute für Katalyse (Germany), under the supervision of Dr. Habil. Evgenii Kondratenko. The research topic dealt with ethanol conversion to H2 and CO2 by means of partial oxidation carried out over supported Pt, Rh and Ru nanoparticles. The greater part of the research work dealt with isobutene alkylation with methanol, in place of formaldehyde, for the production of isoprene via the Prins reaction. The reaction was carried out over different metal phosphates. Main products were isoprene, 2-methylbutenes and dimethyl ether. An investigation on the reaction scheme showed that these products are kinetically primary compounds. Data and investigations shown in this thesis probably will not lead soon to the development of new chemical processes, but they enrich that scientific background that is the pool from which it is possible to design a more sustainable industrial chemistry.